Compressive Strength Comparison Between Plain Concrete and Polyethylene Terephthalate (PET) Mixed Concrete - Karki, Nimesh (KEC Journal of Science and Engineering, 2024)
The construction industry continuously seeks innovative approaches to enhance the mechanical properties of concrete while addressing environmental concerns. This research investigates the quality, mechanical properties, compressive strength of concrete incorporating Polyethylene Terephthalate (PET), a plastic material usually Cold drinks bottle, and compares it with plain concrete. Study involves to replace natural aggregate by an artificial aggregate (PET). PET were introduced into the concrete mix at varying percentages by weight of fine aggregate, following the principle of design mix and comprehensive laboratory testing was conducted to determine the density, quality, Compressive strength and flexural strength of concrete with and without Polyethylene Terephthalate. Non-Destructive test was conducted using Rebound Hammer and Ultrasonic Pulse and Destructive test using Universal Testing Machine. The results reveal that PET mixed concrete slightly decreases the compressive strength of concrete with increasing the percentage of Polyethylene Terephthalate (PET). Density of concrete is 2400kg/m3and concrete up to 6% PET follows the standard value. Based on this study optimum 3.52% of PET by weight can be used in concrete mix. This study underscores the potential of PET fibers as an effective reinforcement material for concrete, contributing to the reduction of plastic waste in the environment. The findings provide valuable insights for the construction industry, highlighting the feasibility of incorporating recycled plastics into concrete mixes to enhance structural performance while promoting sustainability.